Bibliometric Analysis on Mental Health of University Students - Azira Binti Rahim; Ashraff Bin Ruslan; Rozana Binti Othman (Information Management and Business Review, 2024)
This study aimed to examine the research on mental health among university students through bibliometric analysis. The study was conducted using the Biblioshiny package in R-Studio. The study employs quantitative techniques and conceptual frameworks in knowledge discovery. On September 30, 2024, the screening process identified all references to "Mental Health," "University Students," and "Academic Performance" in the article titles inside the Web of Science (WOS). The analysis included 172 documents authored by 682 scholars in 133 journals published in the WOS database between 1996 and 2024. There were 476 affiliations between the universities or institutes where the authors served. However, more research is necessary to determine the effectiveness of interventions, such as setting-based strategies, and to identify risk factors and predictors of mental health among university students. By reviewing prior research, bibliometric analysis enables the researcher to identify the most significant author or article within their area of interest. It offers a comprehensive overview of the research field for academics and professionals interested in it. This study's cluster of mental health research will assist in directing future research areas through thematic maps, which serve as a tool for visualizing and categorizing research subjects based on trends in the literature. These maps assist researchers in comprehending the structure, evolution, and trends within the discipline by grouping similar topics, emphasizing main themes, and pinpointing emerging areas of interest. This will refine the selection and concentration of new research avenues with greater potential to advance the field of mental health studies considerably.